Frequency‐ and state‐dependent effects of hippocampal neural disinhibition on hippocampal local field potential oscillations in anesthetized rats. Issue 10 (12th May 2020) - Gwilt, Miriam; Bauer, Markus; Bast, Tobias
Abstract: Reduced inhibitory GABA function, so‐called neural disinhibition, has been implicated in cognitive disorders, including schizophrenia and age‐related cognitive decline. We previously showed in rats that hippocampal disinhibition by local microinfusion of the GABA‐A receptor antagonist picrotoxin disrupted memory and attention and enhanced hippocampal multi‐unit burst firing recorded around the infusion site under isoflurane anesthesia. Here, we analyzed the hippocampal local field potential (LFP) recorded alongside the multi‐unit data. We predicted frequency‐specific LFP changes, based on previous studies implicating GABA in hippocampal oscillations, with the weight of evidence suggesting that disinhibition would facilitate theta and disrupt gamma oscillations. Using a new semi‐automated method based on the kurtosis of the LFP peak‐amplitude distribution as well as on amplitude envelope thresholding, we separated three distinct hippocampal LFP states under isoflurane anesthesia: "burst" and "suppression" states—high‐amplitude LFP spike bursts and the interspersed low‐amplitudeperiods—and a medium‐amplitude "continuous" state. The burst state showed greater overall power than suppression and continuous states and higher relative delta/theta power, but lower relative beta/gamma power. The burst state also showed reduced functional connectivity across the hippocampal recording area, especially around theta and beta frequencies. Overall neuronal firing was higher in the burst than the other two states, whereas the proportion of burst firing was higher in burst and continuous states than the suppression state. Disinhibition caused state‐ and frequency‐dependent LFP changes, tending to increase power at lower frequencies (<20 Hz), but to decrease power and connectivity at higher frequencies (>20 Hz) in burst and suppression states. The disinhibition‐induced enhancement of multi‐unit bursting was also state‐dependent, tending to be more pronounced in burst and suppression states than the continuous state. Overall, we characterized three distinct hippocampal LFP states in isoflurane‐anesthetized rats. Disinhibition changed hippocampal LFP oscillations in a state‐ and frequency‐dependent way. Moreover, the disinhibition‐induced enhancement of multi‐unit bursting was also LFP state‐dependent.